THE CORRELATIONS AMONG VOCABULARY MASTERY, READING INTEREST AND READING ACHIEVEMENT OF THE TENTH GRADE STUDENTS OF SMA N 4 OF PALEMBANG - Baginda Simaibang; Mulyadi Mulyadi; Wira Lestari (ELTE Journal (English Languange Teaching and Education), 2017)
This study dealt with the inquiry of the correlations among vocabulary mastery, reading interest, and reading achievement of the tenth grade students of SMA Negeri 4 Palembang. The total number of populations were 324 students. The samples for this study were 30 students taken through two stage random sampling technique. Data were collected by adopting questionnaire for reading interest and test for vocabulary and reading achievement. Then, they were analyzed by using r-Product Moment and Multiple Regression. Findings show that there are correlations among vocabulary mastery, reading interest and reading achievement. The data analysis shows that RyX1X2= 0.460 with r2=0.212 and  the criteria of significant test is gotten Fcount. 3.624 > 3.32. Therefore, alternative hypothesis (Ha) was accepted while null hypothesis (Ho) was rejected. In conclusion, vocabulary mastery and reading interest have significant roles to improve reading achievement.Keywords: Correlation, vocabulary, reading interest, reading achievement